Current Situation of Soft Skills Training for Students at FPT Can Tho University - An, Ngo Thi Thuy (VNU Journal of Science: Education Research; Vol 38 No 2DO - 10.25073/2588-1159/vnuer.4620, 2022)
The study was conducted to assess the current situation and needs of soft skills training at FPT University, Can Tho Campus. Total of 545 students studying at the university has given answer a questionaire and carry an in-depth interview. The results show that although the soft skills training program in the university satisfy students in some ways, the quality of those activities is an issue that need to be addressed. Inappropriate choice of soft skills training courses and teaching method or lack of high quality lecturers make bad practice of soft skills training. For the students, in general they are quite confused when learning and practicing soft skills and many of them still lack confidence in their capacity. Based on the analysis results, the study proposes several solutions to improve the quality of soft skills training of the university in the future. Accordingly, in order to solve the mentioned shortcomings, the university needs to build an appropriate training program, select appropriate soft skills courses for each specialized major in each study period, at the same time, stay focus on the lecturers' qualification, and most importantly, create a favorable environment for students to practice soft skills regularly and continuously, to turn theoretical knowledge into practical competence.